PENERAPAN PROGRAM K3 PADA INDUSTRI PENGOLAHAN AIR MINUM DALAM KEMASAN BUMKAL KARYA MANUNGGAL JAYA - Ardi Subhan Zul; Hidayah Qonitatul; Kusuma Damar Yoga; Suwartiningsih Nurul; Rahmadhia Safinta Nurindra (STIE PGRI Dewantara Jombang, 2024)
Factors including irregular working conditions and limited access to Occupational Health and Safety (OHS), training, use of unsafe work equipment, and exposure to hazardous materials are the leading causes of accidents and health problems in the industrial sector, both formal and informal industries. The service aims to plan and assist the K3 program at BUMKal Karya Manunggal Jaya in Serut Village, Gunung Kidul Regency, which has a bottled drinking water management business. Activities were carried out intensively involving 14 employees of BUMKal Karya Manunggal Jaya. From the results of the training, it is known that the trained partners can absorb the training material well. It is reflected in the enthusiasm of the participants as well as the increase in participants' understanding of K3, which is reflected in the results of the pre-test and post-test.